Optimisation of NaOH Concentration for Sustainable Soap Production Using Waste Cooking Oil - Rosman, Mohd Nur Izzuddin; Ibrahim, Siti Aida; Muhammad Yusuf Rosman (Journal of Advanced Mechanical Engineering Applications, 2025)
This study presents a sustainable approach for synthesizing soap bars from WCO. The process involves collecting and filtering WCO, followed by an optimized saponification reaction using alkaline, resulting in soap bars with desirable properties. Comparative analysis reveals that WCO appears darker, with higher free fatty acid content (4.00%) and slightly increased viscosity (79.13 cP) compared to new cooking oil. The study highlights the significant impact of NaOH concentration on soap consistency, where 10% NaOH concentration (sample BS3) has achieved the most stable foam formation. BS3 has no appearance of a gel phase upon cutting and shows 1.78% moisture content. This research emphasizes the utilization of waste cooking oil as a valuable resource for soap production, contributing to waste reduction and supporting sustainable practices within the circular economy framework.